Characterization of metals in PM1 and PM10 and health risk evaluation at an urban site in the western Mediterranean. (June 2018) - Galindo, N.; Yubero, E.; Nicolás, J.F.; Varea, M.; Crespo, J.
Abstract: PM1 and PM10 samples collected in the urban center of Elche during two years were analyzed by Energy Dispersive X-Ray Fluorescence in order to determine the concentrations of the following metals: K, Ca, Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, Sr and Ba. The influence of traffic and Saharan dust intrusions on PM levels and metal content was studied in this work. The results indicate that the coarse fraction was affected more by variations in traffic intensity than the submicron fraction. The concentrations of Ca, commonly used as a tracer of road dust, showed the highest decreases during the weekends due to the reduction in traffic-induced resuspension. In contrast, Saharan events had a greater impact on the levels of other metals such as Ti and Fe, significantly affecting their seasonal variability. High concentrations of V and Ni compared with the values found at larger urban areas were observed. This could be attributed to a significant contribution from soils, Saharan dust and even ship emissions. Enrichment factors calculated using Ti as a reference element indicate that Zn and Cu are predominantly emitted by anthropogenic activities. In fact, Saharan dust intrusions had a minor influence on the average concentrations of these metals. Non-carcinogenic health hazards associated with exposure to airborne metals were lower than the safety threshold (hazard quotient < 1). Carcinogenic risks for Cr (VI) and Ni were between 10 −6 and 10 −4 and, therefore, within the range considered acceptable by the US EPA. Graphical abstract: Image 1 Highlights: The coarse fraction of PM10 affected more by traffic flows than the submicron fraction. High Ca average concentrations associated to road dust resuspension. Outstanding increases of Ti, V, K, Fe and Mn levels during Saharan outbreaks. HQs and CRs below threshold values recommended by the US EPA.